Studi Kajian tentang Evolusi Manajemen Strategi: Studi Kasus pada PT Kereta Api Indonesia (Persero) - Baiq Nurul Suryawati (Sekolah Tinggi Ilmu Ekonomi AMM, 2020)
This study adapted various studies that have been conducted with regard to strategy management reviews. This study reveals the evolution of research in the field of strategy management that has been carried out by Furrer, et al. In his analysis Furrer, et al, identified evolution that shows the direction of integration between corporate-level strategies and competition, therefore, future research questions must be related to the integration of corporations and competition strategies and their implications for company performance in terms of their position in a competitive environment. Meanwhile, referring to what has been revealed by Furrer, et al., Several companies in Indonesia can be identified as currently undergoing what is called the Knowledge-based Theory of Firm phase, where the phase is the phase of knowledge creation as the basis for sustainable competitive advantage. Case study at PT. Kereta Api Indonesia (Persero) shows the findings of the dependence of PT. KAI through loans or binding contracts so that competitive advantage cannot be achieved. The recommendations suggested to be implemented for PT. KAI is not to dwell on the second position of the evolutionary phase of strategy management according to Wade and Schneberger, the Resource Dependency Theory phase. This is needed for Indonesian companies to win global competition.